Understanding the effect of Facebook in the relationship of self-concept and brand image on smartphone brand satisfaction - Guillen, Nelson B., Jr. (Animo Repository, 2018)
The purpose of this research is to investigate the effect of Facebook in the relationship of self-concept and brand image on smartphone brand satisfaction which was operationalized by identifying self-congruity (SC), behavior (B), and brand satisfaction (BS). The SBI model was used in this study. This study had randomly selected 300 millennial respondents ages 19-29 years old using Facebook Insights for the survey poll (N=300). Confirmatory factor analysis and model testing were conducted using structural equation modeling (PLS-SEM). In the overall framework, results showed that SC significantly affects B and B significantly affects BS while BS significantly affects SC so as SC significantly affects BS (with p-values ≤ 0.01). For the T-test, coefficients were all above 1.96 which is considered significant at 0.05 or 95% confidence level. The study suggests that marketers should try develop product images consistent with the self-concepts of their target audience whether online or offline. With this trend, they need to develop appropriate customer service training for improved engagement with Facebook as another social medium and a prospective sales platform.